103 UK national and regional trends in cardiovascular magnetic resonance usage - the british society of CMR 2019 survey results. (17th July 2020) - Keenan, Niall; Captur, Gabriella; McCann, Gerry; Berry, Colin; Myerson, Saul; fairbairn, tim; Hudsmith, Lucy; O'Regan, Declan; Westwood, Mark; Greenwood, John
Abstract : Background: / Introduction Cardiovascular magnetic resonance (CMR) is an advanced imaging modality recommended in guidelines for a wide range of indications. Variations in use of CMR nationally and internationally may be due to challenges in accessing this technology. The British Society of CMR (BSCMR) commissioned a survey to retrospectively appraise scan volume, indications, waiting times, scanners and staffing across all CMR units in the UK in 2018. Methods: An online survey instrument was developed and approved for use in this study by the BSCMR board. The survey was mailed to the leads of all CMR units currently in the UK. Responses were analysed by region and country and interpreted alongside publicly available national statistics on population size. Results: The survey response rate was 100% (data from all 84 UK CMR units in Table ). The UK performed a total of 102, 886 scans in 2017, and 117, 967 in 2018 representing a 1-year 14.7% increase and a 10-year increase of 573% when considering survey data from 2008 (total n was 20, 597). For comparison in 2017 the USA performed 26, 796 CMR scans on 58.5 million Medicare beneficiaries (406 scans per million population) while the UK performed 1, 548 per million that year (3.8X higher). By head of population in 2018 there were 1, 776 CMR scans per million people, with significant variation nationally and regionally, e.g. 4, 256 per million in London vs. 396 per million in Wales (Figure ). Mean number of scans per unit was 1, 404, (range 98-10, 000) with wide variation in referral to diagnostic (RTD) scan times (mean RTD 45.7 days, range 5-180). Twenty-five units (29.8%) reported mean outpatient waiting times in excess of 6 weeks, and 8 (11.9%) reported waiting times of ≥3 months (e.g. 28.5 days waiting time in London vs. 180 days in Northern Ireland, Figure 1 ). Clinical indications for CMR were: heart failure 20.7%, cardiomyopathy 26.6%, function and viability 22.0%, stress perfusion 23.7%, acquired vascular disease 5.4%, valvular heart disease 5.4%, myocarditis/pericardial disease 9.9%, stress 24%, paediatric / congenital heart disease 10.1%, cardiac transplant 0.4%, others e.g. cardiac masses 3.3%, with overlap between indications. There were 358 consultants reporting CMRs in 2018 of whom 234 (65%) cardiologists and 124 (35%) radiologists. 81% of units had a CMR service for patients with pacemakers and defibrillators. Conclusion: The 2019 BSCMR CMR UK survey provides valuable insight into the 'real-world' state of CMR usage nationally. The 10-year growth in CMR usage at 573% has been remarkable, but not uniform across regions of England and devolved nations of the UK, with wide disparities in terms of use, access and waiting times. In regions where CMR usage is low or waiting times long, there is a concern that patients are being managed without the timely added benefits that this advanced cardiac imaging modality can bring to clinical care. The BSCMR is committed to take action to make access to CMR equitable across the UK. Conflict of Interest: None